Nilai-nilai Filosofis yang Terdapat pada Yoga Sutra Patanjali - Siti Nurlaili M (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2004)
Yoga Sutras of Patanjali is considered the defenitive work on traditional yoga, and is well known as the first ecer written. The Yoga Sutras of Patanjali dates back to around 1st and 3st century A.D. In this classic, Patanjali articulates the yogic cosmology through 195 Sutras (wisdom pearls). These sutras together form a tepestry of knowledge derived from many yogic traditions into a set of pity equations. According to the Yoga Sutras, the ultimate aim of Yoga is to reach